Role of miRNAs in the Chikungunya virus replication and pathogenesis - Nangare, Rohini A.; Gajbhiye, Virendra; Karpe, Yogesh A. (Frontiers in Virology, 2024)
Chikungunya virus (CHIKV) is a vector-born alphavirus responsible for chikungunya fever with clinical manifestation of polyarthritis transmitted by Aedes aegypti and Aedes albopictus. Establishing viral pathogenesis needs host machinery modulation, and the microRNAs (miRNA) modulate host cellular machinery to establish the infection or inhibit viral replication. miRNAs are the small noncoding RNA that control the gene. They are essential in cell differentiation, growth, development, and apoptosis. It also affects disease progression, cancer, and viral infection. CHIKV infection causes differential expression of miRNA, and miRNA has target genes involved in different cellular functions. These target genes may be crucial in CHIKV replication and cell growth. Suppression or overexpression of these miRNAs may have been linked with CHIKV pathogenesis by regulating immune and signaling pathways. Identification of biomarkers in disease progression through the study of circulating miRNAs during CHIKV infection is an emerging field. Therefore, understanding miRNAs' differential expression and function during CHIKV infection is essential. The detailed studies on the miRNA-mediated regulatory network will provide new ways to develop miRNA-based therapies.